تيمة الحرب في قصة "الدروب" للطاهر وطار - دقي، حياة (جامعة مولود معمري تيزي وزو - كلية الآداب واللغات - مخبر تحليل الخطاب, 2021)
يهتم البحث بجنس القصة القصيرة عند الطاهر وطار وأبرز خصائصها الفنية بالتركيز على تيمة الحرب في أكثر القصص توظيفا لها وهي قصة "الدروب"، التي أتاحت بمركزيتها ذلك الحضور المميز والقوي لتيمة الحرب ولتقديم الواقع باقتدار ووعي فني، هذا الذي نقف عنده بتسليط الضوء على القصة وتحليلها والبحث في موضوعها وجماليات التشكيل السردي الذي تقوم عليه.
This research is interested about the genre of the short story in Taher Wattar’s stories and its most prominent artistic characteristics. It has focused on the theme of war in stories, “The Paths” is the story that makes the most use of this theme, which its centralization enabled the distinctive and strong presence of the theme of war and presented reality with an ability and artistic awareness. This is what we highlight on the story and analyzing it and researching into its topic and the aesthetics of the narrative forms based on.
Keywords: القصص العربية -- الأدب الشعبي -- النقد الأدبي -- وطار، الطاهر، ت. 2010 م